2019
DOI: 10.1097/rli.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Does Age Interfere With Gadolinium Toxicity and Presence in Brain and Bone Tissues?

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 98 publications
5
29
1
1
Order By: Relevance
“…Previously unknown site of Gd accumulation was identified by Delfino et al, who observed Gd deposition in the periodontal tissues in murine model with induced renal disease, using SR-XRF and LA-ICP-MS 47 . Interesting results showing differential accumulation of Gd by different bone tissues -cortical, trabecular bone and bone marrow in juvenile and adult rats by ICP-MS were published by Fretellier et al 48 . An interesting line of research -usage of GBCAs in pregnancy and potential effect of Gd on foetus, were investigated by Prola-Netto et al in rhesus macaques, and although only extremely low levels of Gd were found in juvenile tissues after in utero exposure, femur was identified as a site of consistent Gd retention in all the animals 49 .…”
Section: Analysis Ex Vivo Localization Within Bonementioning
confidence: 99%
“…Previously unknown site of Gd accumulation was identified by Delfino et al, who observed Gd deposition in the periodontal tissues in murine model with induced renal disease, using SR-XRF and LA-ICP-MS 47 . Interesting results showing differential accumulation of Gd by different bone tissues -cortical, trabecular bone and bone marrow in juvenile and adult rats by ICP-MS were published by Fretellier et al 48 . An interesting line of research -usage of GBCAs in pregnancy and potential effect of Gd on foetus, were investigated by Prola-Netto et al in rhesus macaques, and although only extremely low levels of Gd were found in juvenile tissues after in utero exposure, femur was identified as a site of consistent Gd retention in all the animals 49 .…”
Section: Analysis Ex Vivo Localization Within Bonementioning
confidence: 99%
“…Whilst there was an initial washout between 1 h and 1 day (81.69 ± 67.46 nmol Gd/g tissue and 18.46 ± 1.96 nmol Gd/g tissue, respectively), levels of gadolinium detected remained consistent up to 20 weeks (14.00 ± 0.06 nmol Gd/g tissue) post-dosing (Davies et al 2021 ). Age has been shown to have an impact on bone gadolinium retention, with a higher concentration of gadolinium in the bone marrow of gadodiamide-treated juvenile rats compared with adults, but not noted in any other tissues analysed (Fretellier et al 2019 ). Among animal models used to mimic BBB disruption that is seen in human CNS disease, one such model uses lipopolysaccharide (LPS) to stimulate sepsis in rats, and this results in an increase in bone retention with gadobenate (0.2 mmol/kg) administration compared to control animals (394.22 ng/g ± 62.6 and 292.52 ng/g ± 43.9, respectively).…”
Section: Gadolinium Distribution In Humans and Animalsmentioning
confidence: 99%
“…Gadolinium retention in the skin of rodents has been demonstrated in multiple studies and can persist for up to 1 year post-dosing (Pietsch et al 2009 ; Murata et al 2016a ; Lohrke et al 2017 ; Bussi et al 2018a , b ; Fretellier et al 2019 ). In a comprehensive study, rats were given a cumulative dose of 12.5 mmol/kg (20 times the human equivalent dose) of either a linear GBCA (gadodiamide, gadopentetate, gadobenate or gadoversetamide) or a macrocyclic GBCA (gadoteridol, gadoterate or gadobutrol) and skin biopsies were taken at various time points up to 364 days post-dosing (Pietsch et al 2009 ).…”
Section: Gadolinium Distribution In Humans and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. in der Haut durch die Pathogenese der NSF, aber auch im Knochen [46,47]. Die absoluten Konzentrationen von Gadolinium waren dabei in Haut und Knochen deutlich höher als im Gehirn [48]. Auch in peripheren Nerven und dem Rückenmark waren nach Verabreichung von linearen GBCAs im Tierversuch höhere Gadolinium-Konzentrationen als im Gehirn bestimmt worden, wobei das gemessene Gadolinium nach Injektion von Makrozyklen in diesen Lokalisationen insgesamt geringer nachgewiesen wurde [49].…”
Section: Gadolinium-retention Im Gehirnunclassified